An Estimation of Technical Efficiency of Red Chili Pepper's Growers in Central Bangka - Purwasih, Rati; Bahtera, Novyandra Ilham; Yulia (Indonesian Journal of Agricultural Research, 2020)
In Central Bangka, The red chili pepper's productivity is still considered at low level. It is corroborated from comparison between the productivity of red chili pepper which is computed as 35.6 quintal per hectare while the potential productivity of the genetics of red chili pepper is 200-220 quintal per hectare. It is presumed that the productivity of red chili pepper is technically inefficient. The aim of the study is to analyze factors that affect the production of red chili pepper and the technical inefficiency. The study also determines the level of technical efficiency of red chili pepper on smallholders who participate in the agriculture productivity improvement program in Central Bangka Regency. Survey was carried out to collect the data with purposive sampling method. The criteria of respondents were those red chili pepper smallholders who had involved with the agriculture productivity improvement program. The total sampled respondents were 43 smallholders. Stochastic frontier analysis with the Maximum Likelihood Estimate was used to analyze the data. The study discovered the factors that affect the production of red chili pepper were labor, potassium fertilizer, insecticide, and fungicide. Furthermore, the productivity of red chili pepper was considered as technically inefficient which was shown from the average score of technical efficient, 0.54. Finally, the study revealed that side job became factor that could increase the technical inefficiency of red chili pepper farming activity while the frequency of attending the empowerment program and farmer field school were otherwise.